Review and synthesis: dynamism of classical and holistic drought indices and indicators - Hirwa, Hubert (Frontiers in Water, 2025)
Droughts are complex and recurring natural hazards throughout the ecosystems and impact many sectors of society. Droughts have complex spatiotemporal behaviors; therefore, monitoring them is a challenging task. Drought monitoring has depended chiefly on climate-based indices and indicators, thus deemed useful in many scenarios. This review aims to explore classical and holistic drought indicators/indices for unravelling their usefulness and associated limitations. Given that they offer a broadened spatial perspective of drought conditions and fluctuations over large areas, climate-based drought index maps may be of limited use. Precise evaluations of drought are necessary for efficient monitoring and assessment of the condition. Here, this review examined more than 50 indices/indicators for their sensitivity to input data requirements, spatiotemporal scales, strengths, and weaknesses. Also, an analysis was carried out based on the previous studies to identify hotspots and show the dissimilarity in the results yielded by different indices/indicators. None of these indices is typically inclusive enough to provide a broad-gauge assessment and determine appropriate actions. New and enhanced geospatial intelligence-based drought indices and earth observations are needed to identify, classify, and communicate real-time drought-related phenomena and offer an in-depth breakdown of the constraints and requirements of novel indicators and data difficulties.